National Mental Model and Competitiveness: Transformation Towards Achieving and Progressive Behavior - Ali Maksum (Faculty of Psychology, Universitas Surabaya, 2014)
Mental Model is believed to be a crucial issue for turning this nation to be a developed nation. There are seven mental qualities that delay development, which are quality- despising mentality, shortcut mentality, vertical-feudalistic dependency, easy to complain and to find excuses mentality, power-oriented, extrinsic-oriented, myth and fate believer. It will require reconstruction and transformation to have an achieving and progressive mental model. There are seven mental qualities required to improve this nation, which are adaptive to changes, appreciative of time and resources, independent and responsible, achieving- oriented, trusting science, having self-control and committed to morality. In order to bring about this constructive mental model, quality education and constructive habits are needed to optimize critical thinking. Hence it will strengthen the process of constructive habits and reinforce culture of accountability, starting from family upbringing, school education and interaction in the society. Model mental diyakini merupakan persoalan krusial bangsa ini untuk menjadi negara maju. Ada tujuh kualitas mental yang menghambat kemajuan, yakni mental yang meremehkan mutu, suka jalan pintas, ketergantungan vertikal-feodalistik, gampang mengeluh dan mencari alasan, orientasi kekuasan, orientasi ekstrinsik, dan percaya mitos dan nasib. Dibutuhkan rekonstruksi dan transformasi menuju model mental yang lebih prestatif dan progresif. Ada tujuh kualitas mental yang dibutuhkan bangsa ini untuk menjadi lebih baik, yakni adaptif terhadap perubahan, menghargai waktu dan sumberdaya, kemandirian dan tanggung jawab, berorientasi capaian, percaya pada ilmu pengetahuan, pengendalian diri, dan komitmen moral. Untuk mewujudkan model mental yang konstruktif tersebut dibutuhkan pendidikan yang bermutu dan akuntabel, dengan mengoptimalkan fungsi berpikir kritis, memperkuat proses pembiasaan konstruktif, dan memperkokoh kultur akuntabilitas, mulai dari pengasuhan di keluarga, pembelajaran di sekolah, dan interaksi di masyarakat.